Lower Elementary School Student Non-Locomotor Movement Profile During COVID-19 Pandemic - Melinda, Cellin; Gumilar, Agus; Nuryadi, Nuryadi (TEGAR: Journal of Teaching Physical Education in Elementary School, 2023)
This study aimed to construct a profile related to the basic non-locomotor movement skills of elementary school students during the COVID-19 pandemic. The survey was conducted on 53 elementary school students aged 6–8 years of an elementary school in Bandung. The instrument of the study was an instrument for assessing non-locomotor movement skills developed by Gallahue related to stability skills including beamwalk (walking on a beam), one foot balance (standing on a beam with one leg), and dodging. The findings showed that the motor skill stages of lower elementary school students of elementary school in Bandung during the pandemic included three stages, namely the initial stage (6% for the beam walk test, 11% for the one foot balance test, and 15% for the dodging test), the elementary stage (64% for the beam walk test, 70% for one foot balance, and 60% for the dodging test), and the mature stage (30% for the beam walk test, 19% and 25% for the one foot balance and the dodging test, respectively).